Pentingnya relevansi informasi perpajakan di perusahaan - Al Iqbal , Kalam (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
One measure of the extent to which the government is successful in controlling economic resources is seen from the percentage of tax revenue from GDP. Indonesia had a tax-to-GDP ratio of 11.6% in 2019, below the Asia and Pacific (24) average of 21.0% of 9.5 percentage points. Efforts to optimize the source of tax revenue, one of which can be achieved by increasing tax revenue from the company. Companies can increase taxes if they have good financial performance, which of course is supported by investors. However, investors need to have information to make their investment decisions. This article aims to determine the importance of the relevance of information to the value of the company. The methods used in this article are systematic review and meta analysis. The results of this study strengthen the results of previous studies, namely the relevance of information on taxes, especially income taxes and deferred taxes can increase firm value.